Elective treatment of intracranial stenosis with the balloon-expandable Pharos Vitesse stent: 30-day stroke rate and complications. (7th February 2014) - von Schoenfeldt, Patrick; Krützelmann, Anna; Bußmeyer, Matthias; Mpotsaris, Anastasios; Rosenkranz, Michael; Fiehler, Jens; Weber, Werner; Buhk, Jan-Hendrik
Abstract : Background and purpose: Analysis of procedural results and 30-day outcome after intracranial angioplasty and stenting (ICAS) with the balloon-expandable Pharos Vitesse stent system in carefully selected high-risk patients in two high-volume neurovascular centers. Materials and methods: 92 patients scheduled for elective ICAS using Pharos Vitesse between August, 2008 and August, 2011 were included. All patients showed high-grade intracranial stenosis and recurrent ischemic events despite best medical treatment at that time. The stroke rates and complications were divided into procedural and 30-day short-term events. Results: Successful stent placement was achieved in all but one patient. Ischemic procedural complications occurred in three subjects. 30-Day complications and strokes were seen in four patients: two minor ischemic strokes, one fatal hemorrhage and one non-stroke-related death. Overall, strokes occurred in 6 out of 92 patients (6.5%, 95% CI 3.0% to 13.5%). The total stroke and death rate was 7.6% (95% CI 3.7% to 14.9%). No significant correlation with previously reported risk factors could be found, although a higher rate of ischemic strokes (four out of five) in the posterior circulation was recorded. Conclusions: In patients with intracranial stenosis who experience recurrent ischemic events despite best medical treatment, ICAS, using the balloon-expandable Pharos Vitesse stent, may still be considered as an individual treatment option in high-volume neurovascular centers.